Analisa Pengaruh Variasi Jumlah Nozzle Dengan Memanfaatkan Ketinggian Aliran Air Terhadap Daya Listrik Yang Dihasilkan Turbin Pelton - Yasir, La Ode; Balaka, Ridway; Endriatno, Nanang (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2022)
The performance of a Pelton turbine is influenced by the height, flow velocity, blade angle, number of nozzles, flow size and number of blades and nozzle spray distance. The purpose of this study was to determine the effect of variations in the number of nozzles and nozzle angles on the power produced by the PRLton turbine. The test results show that the more nozzles used, the greater the power generated and the smaller the nozzle angle, the greater the power generated. In position I using 1 nozzle, at an angle of 25o the electrical power produced is 6.16 Watt, at an angle of 30o the electric power produced is 2.65 Watt, at an angle of 45o the electrical power generated is 0.1 Watt. While in position II using 2 nozzles, , at an angle of 25o the electrical power produced is 7.56 Watts, at an angle of 30o the electrical power generated is 3.76 Watts, at an angle of 45o the electrical power generated is 0.24 Watts.Keywords: Electric power, Nozzle, Pelton turbine